Joseph Twist. Mystical Islam and Cosmopolitanism in Contemporary German Literature. Openness to Alterity. Camden House, 2018. - Frederike Middelhoff (Studies in 20th & 21st Century Literature, 2019)
Review of Joseph Twist. Mystical Islam and Cosmopolitanism in Contemporary German Literature. Openness to Alterity. Camden House, 2018. xii + 216 pp.
Keywords: Zafer Şenocak; SAID; Feridun Zaimoglu; Navid Kermani